2015
DOI: 10.1155/2015/846743
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles Using Extract of Oak Fruit Hull (Jaft): Synthesis and In Vitro Cytotoxic Effect on MCF-7 Cells

Abstract: A green synthetic approach by using oak fruit hull (Jaft) extract for preparation of silver nanoparticles (AgNPs) was developed and optimized. Parameters affecting the synthesis of AgNPs, such as temperature, extract pH, and concentration of extract (ratio of plant sample to extraction solvent), were investigated and optimized. Optimum conditions for the synthesis of silver nanoparticles are as follows: Ag+ concentration, 1 mM; extract concentration, 40 g/L (4% w/v); pH = 9 and temperature, 45°C. Biosynthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(59 citation statements)
references
References 22 publications
6
51
2
Order By: Relevance
“…UV-Vis spectroscopy in this study confirmed silver nanoparticles formation since abroad absorption peak ranging from 400-450 nm is a characteristic band for the Ag, arising from the excitation of longitudinal plasmon vibrations of AgNP in the solution [35]. On the other hand, TEM images results were well documented by the observations recorded by Singh et al; Heydari and Rashidipour [36,37]. when AgNPs prepared by Oak fruit hull.…”
Section: Discussionsupporting
confidence: 82%
“…UV-Vis spectroscopy in this study confirmed silver nanoparticles formation since abroad absorption peak ranging from 400-450 nm is a characteristic band for the Ag, arising from the excitation of longitudinal plasmon vibrations of AgNP in the solution [35]. On the other hand, TEM images results were well documented by the observations recorded by Singh et al; Heydari and Rashidipour [36,37]. when AgNPs prepared by Oak fruit hull.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the cytotoxic mechanism of AgNPs is predominantly based on the induction of reactive oxygen species (ROS). Specifically, exposure to silver nanoparticles triggers depletion in glutathione level, elevation of ROS levels, lipid peroxidation, and increased expression of ROS responsive genes, leading to DNA damage, apoptosis, and necrosis (Haider and Kang 2015).…”
Section: −1mentioning
confidence: 99%
“…Compared with other methods, biological methods using microorganisms (7,8), enzymes (9), and plants or plant extracts like Nothapodytes nimmoniana (Graham) Mabb. fruit extracts (10), Alternanthera dentate aqueous extract, Acorus calamus and Boerhaavia diffusa plant extracts (11), Allophylus serratus leaf and leaf-derived callus extracts (12) are environmentally friendly and alternatives to chemical and physical methods for the synthesis of AgNPs (13). Synthesizing nanoparticles using plant extracts can be advantageous over other biological processes by omitting the elaborate process of maintaining cell cultures (14), complex extraction and purification processes (15) and it also allows easy scale up to produce larger amounts of nanoparticles that are free of contamination and have well-defined size and morphology (16).…”
Section: Introductionmentioning
confidence: 99%